Updating MISEV: Evolving the minimal requirements for studies of extracellular vesicles. Issue 14 (25th December 2021) - Witwer, Kenneth W; Goberdhan, Deborah CI; O'Driscoll, Lorraine; Théry, Clotilde; Welsh, Joshua A; Blenkiron, Cherie; Buzás, Edit I; Di Vizio, Dolores; Erdbrügger, Uta; Falcón‐Pérez, Juan M; Fu, Qing‐Ling; Hill, Andrew F; et al.
Abstract: The minimal information for studies of extracellular vesicles (EVs, MISEV) is a field‐consensus rigour initiative of the International Society for Extracellular Vesicles (ISEV). The last update to MISEV, MISEV2018, was informed by input from more than 400 scientists and made recommendations in the six broad topics of EV nomenclature, sample collection and pre‐processing, EV separation and concentration, characterization, functional studies, and reporting requirements/exceptions. To gather opinions on MISEV and ideas for new updates, the ISEV Board of Directors canvassed previous MISEV authors and society members. Here, we share conclusions that are relevant to the ongoing evolution of the MISEV initiative and other ISEV rigour and standardization efforts.